PENGARUH DEMOGRAFI DAN SOSIAL BUDAYA MUSTAHIK TERHADAP KEBERHASILAN PENGENTASAN KEMISKINAN DI KABUPATEN LOMBOK TIMUR - Singandaru, Adhitya Bagus; Hidayat, Ali Akbar; Fadlli, Muhammad Dzul; Wafik, Ahmad Zaenal (Elastisitas : Jurnal Ekonomi Pembangunan, 2024)
This research was conducted in East Lombok Regency using mixed methods. The purpose of this study was to determine how the influence of demographic and socio-cultural factors of productive zakat recipients/mustahik affects the success of poverty alleviation through productive zakat schemes carried out by the National Amil Zakat Agency (Baznas) of East Lombok Regency. The number of respondents studied in this study were 100 respondents. The variables studied consisted of 9 (nine) independent variables covering demographic factors (number of family members, gender, education level, age, occupation, and business location) and socio-cultural factors (social habits in business, work culture in the household, and religiosity) and 1 (one) dependent variable seen from business success. The variable of business success is seen from the achievement of net profit per month from the business run at a minimum of Rp 2,201,832. This figure is derived from the poverty line set by BPS of Rp 550,458/capita/month with a family of 4 people. The results show that of the nine variables, only the age variable has a significant effect on the success of mustahik businesses. Mustahiks aged <45 are estimated to be 0.881 times more likely to succeed than mustahiks aged >46 years. Meanwhile, other variables such as the number of family members, gender, education level, occupation, business location, social habits in business, work culture in the household, and religiosity, have no significant effect on the success of mustahik businesses.